Your browser version is outdated. We recommend that you update your browser to the latest version.

Quiz:

Remember the Phase: (Please Excuse My Dear Aunt Sally)

Questions:

1. 3r 2+ 4t (Find the value of each expression when r = 3 and t = -2
2. –r + 5t -2t + 9r
3. 6r -3t2 + 4t -2r
4. 4rt – 2r(8 +t)
5. 2a + 3b - 4c –(5a + 4b) (Find the value of each expression when a = -3, b =6, and c=1)
6. 4(a – b + 2c) + c(a – 3)
7. 3c - 3ab + b(3a +c)
8. 5b + 2b(c –a) + 3ab
9. 6(3w + x) +2y – 3(w – z)
10. w2 – 3x + 5(z + 4) -10 (1/2z + y)

Find the value of each expression when r = 3 and t = -2

1. 3r 2+ 4t

3(9) = 27

4(-2) = -8

Answer: 27 -8 = 19

1. –r + 5t -2t + 9r

-r +9r = 8r

8(3) =24

5(t) – 2(t) = 3t

3(-2) = -6

Answer: 24 - 6 =18

1. 6r -3t2 + 4t -2r

6r – 2r = 4r

4(3) = 12

-3(t2) + 4t = 1(-2) 2

1(-2) 2 = -4

Asnwer: 12 – 4 = -8

1. 4rt – 2r(8 +t)

-2r(8) = -16r

-2r(t) = 2rt

-16(3) = -48

4rt – 2rt = 2rt

2(3) = 6

6(-2) = -12  (this is the 2(r) & (t) together) add & multiply again)

Answer: -48 + -12 = 60

Find the value of each expression when a = -3, b =6, and c=1

1. 2a + 3b - 4c –(5a + 4b)

2a – 5a = 3a

3b – 4b = b

-4c = -4c

= 3a + b -4c

Replace variables with digits: when a = -3, b =6, and c=1

3(-3) = -9

B * 6 = 6

-4(1) = -4

-9 + 6 = -3

-3 -4 = -1

Answer: -1

1. 4(a – b + 2c) + c(a – 3)

a + b + c

4(a) = 4(a)

4(b) = 4(b)

4(2c) = 8(c) - (ac1(-3) = -3c) = 8c -3c = 5c

+

C = 1(-3) = – 3

4(-3) – 4(6) + 5(1) -3

-12 – 24 + 5 -3 = Turn left (-12+ -24 = -36)

-36 + 5 = Turn right (-36 + 5 = 31)

-31 + – 3 = Turn left (-31 + -3 = -34)

Answer: -34

1. 3c - 3ab + b(3a +c)

-3ab + 3ab = 0

3(c) + b(c) =  3*1 + 6*1 = 3 + 6

= 3 + 6 = 9

Answer: 9

1. 5b + 2b(c –a) + 3ab

-2ab + 3ab = ab

5b + 2bc + ab

5(6) + 2(6)(1) +(-3)(6) =

5 * 6 = 30

2 * 6 = 12 * 1 = 12

-3 * 6 = -18

30 + 12 – 18 = 24

Answer: 24

Find the value of each expression when w = 1, x = -2, = y = 3, and z = -4

(Please Excuse My Dear Aunt Sally)

1. 6(3w + x) +2y – 3(w – z)

w, x, y, z

6(3)(w)  = 18 * 1 = 18

-3(w) = -3

18 – 3 = 15

6(x) = 6 * -2 = -12

+ 2y  = 2 * 3 = 6

-3(z) = -3 * -4 = -12 (multiplied then stay negative) (add then it is positive)

15 -12 + 6 -12 = -3 (How: (15-12 = 3) (3+6= 9) (9 – 12 = -3)

Answer: -3

1. w2 – 3x + 5(z + 4) -10 (1/2z + y)

w2, x, y, z

12 = 1 * 1 = 1

-3x = -3(-2) = 6

5(z)  -10(1/2) = 5 – 5 = 0

5(4) = 20

-10(y) = -10(3) = -30

1 + 6 + 20 -30 = -3 Answer: